The economic and fiscal contribution of US investment in Ireland - Walsh, Keith (Statistical and Social Inquiry Society of Ireland, 2011)
Multinational companies from the United States of America are important sources of foreign investment in Ireland. The role of these companies in the Irish economy has been previously documented and is reviewed briefly. The main contribution of this paper is to present for the first time data on the fiscal impact of US companies in Ireland. The results show that US companies are significant sources of tax revenue. Over the last decade US companies have consistently paid around one third of the annual corporation tax revenue collected in Ireland. US companies also make large payments of value added tax, excise duty and income tax ? the latter is due to the approximately one hundred thousand people employed in Ireland by US companies and indicates the substantial nature of US investment in this country. The sectoral composition of tax revenue from US companies and employment patterns over time are also examined.
read before the Society, 9 December 2010
Keywords: foreign direct investment; Unites States; fiscal policy; Ireland; 314.15